2016
DOI: 10.1002/2015gl067443
|View full text |Cite
|
Sign up to set email alerts
|

Formation of layers of methane in the atmosphere of Mars after surface release

Abstract: Simulations with a general circulation model for the atmosphere of Mars show that surface emissions of methane can result in a highly nonuniform vertical distribution throughout the atmosphere, including the formation of layers, during the first weeks after the release. The fate of the released methane is determined by the global circulation pattern at the time of the release, and the methane can be transported to locations over the planet that are remote from the emission site. It typically takes several week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
1
19
1
Order By: Relevance
“…However, if rapid vertical transport occurs under some conditions (e.g., Viscardy et al, 2016, Holmes et al, 2017, the CH4 mixing ratio could be significantly enhanced in the middle atmosphere. A constant vertical load then could imply a middle atmosphere mixing ratio much greater than the mean 1 ppbv mixing ratio assumed here.…”
Section: Results and Sensitivitiesmentioning
confidence: 99%
“…However, if rapid vertical transport occurs under some conditions (e.g., Viscardy et al, 2016, Holmes et al, 2017, the CH4 mixing ratio could be significantly enhanced in the middle atmosphere. A constant vertical load then could imply a middle atmosphere mixing ratio much greater than the mean 1 ppbv mixing ratio assumed here.…”
Section: Results and Sensitivitiesmentioning
confidence: 99%
“…Gases like C 2 H 2 or C 2 H 6 are also involved in serpentinization processes and will be observed by NOMAD along with CH 4 and H 2 O. Viscardy et al (2016) showed in a model study that the vertical distribution of CH 4 can be highly non-uniform and variable after an emission from the surface. This is most interesting and was never conjectured before.…”
Section: Organicsmentioning
confidence: 99%
“…With the dense diurnal coverage (12 to 24 vertical profiles per sol sampling all longitudes at regular intervals), combined with similar detections by ACS's MIR spectrometer, we will not only be able to confirm the presence or absence of CH 4 in the Martian atmosphere (down to ppt level) but also to monitor its variability and try to relate it to surface emissions. Therefore this finding by Viscardy et al (2016) is highly important to NOMAD and the TGO mission, as it provides a new way to relate CH 4 to surface processes. A recent modeling study by investigates the interpretation of CH 4 vertical profiles to be returned by the NOMAD instrument, with constraints imposed on distinguishing between different emission scenarios.…”
Section: Organicsmentioning
confidence: 99%
“…The existence of methane on Mars has recently been confirmed with an in situ detection by the NASA Curiosity rover [ Webster et al , ]. Recent modeling studies of methane surface release have shown that methane can form layers in the atmosphere [ Viscardy et al , ] and that surface releases of methane could potentially reconcile past observations from multiple different instruments [ Holmes et al , ]. The fact that a surface release of methane can evolve into a distinct atmospheric layer suggests that the local observations by the NASA Curiosity rover and past column observations by other instruments [ Mumma et al , ; Fonti and Marzo , ; Geminale et al , ; Villanueva et al , ] can potentially be reconcilable.…”
Section: Introductionmentioning
confidence: 99%
“…Previous modeling studies investigating the evolution of a methane source have been limited by the use of modeled wind fields [ Lefèvre and Forget , ; Viscardy et al , ]. For the methane emission scenarios in this study, temperature retrievals from the Thermal Emission Spectrometer (TES) are assimilated using a modified form of the Analysis Correction (AC) scheme [ Lewis et al , ].…”
Section: Introductionmentioning
confidence: 99%